2019
DOI: 10.1177/1755088219829884
|View full text |Cite
|
Sign up to set email alerts
|

Responding to terrorism with peace, love and solidarity: ‘Je suis Charlie’, ‘Peace’ and ‘I Heart MCR’

Abstract: This article explores the affective responses to terrorist attacks in Western Europe, visually manifested through the memes ‘Je suis Charlie’, ‘Peace’, and ‘I heart MCR’ . By invoking the universal peace and solidarity signs, these responses mobilised an iconic repertoire that framed the responses as peaceful retaliations to terrorist attacks in solidarity with the victims and in that respect, helped to visualise and foster positive emotions in times of crisis. Indeed, the memes were articulated as the antidot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…A wealth of scholarship has demonstrated that visual media help to shape possibilities in global politics (Hansen 2011;Heck and Schlag 2013;Hoskins and O'Loughlin 2010;Merrin 2018). Yet, despite this, very little IR scholarship engages with how people actually interpret, make sense of, and express emotions towards the visual media that they view (Beattie et al 2019;da Silva and Crilley 2017;Eroukhmanoff 2019;Gillespie et al 2010;O'Loughlin 2011;Pears 2016). This paper addresses this gap by demonstrating how the concept of 'affective investment' can benefit the study of visual global politics.…”
Section: Interrogating Emotions and Images Of Warmentioning
confidence: 98%
“…A wealth of scholarship has demonstrated that visual media help to shape possibilities in global politics (Hansen 2011;Heck and Schlag 2013;Hoskins and O'Loughlin 2010;Merrin 2018). Yet, despite this, very little IR scholarship engages with how people actually interpret, make sense of, and express emotions towards the visual media that they view (Beattie et al 2019;da Silva and Crilley 2017;Eroukhmanoff 2019;Gillespie et al 2010;O'Loughlin 2011;Pears 2016). This paper addresses this gap by demonstrating how the concept of 'affective investment' can benefit the study of visual global politics.…”
Section: Interrogating Emotions and Images Of Warmentioning
confidence: 98%
“…Social media is also used by radical far-right actors to promote racism, misogyny, and conspiracy theories that have resulted in acts of violence in places such as Charleston and Christchurch (Conway 2020). At the same time, social media is integral to how people nowadays respond to terrorism through expressions of solidarity (Eroukhmanoff 2019). International organisations have also been drawn to social media to rally global public support for policies such as the UN's Sustainable Development Goals; to secure funding; and to disseminate a shared and coherent foreign policy, as in the case of NATO (Wright 2019).…”
Section: Visual Narratives and International Relations In The Digitalmentioning
confidence: 99%
“…These attacks now enter people's lives not only via broadcast and printed media but also via social media. The latter allows people to rapidly respond to terrorism by, among other things, digitally sharing expressions of togetherness (Eroukhmanoff, 2019). The use of social media in this way can also occur later, including around anniversaries, when terror attacks are often commemoratively reactivated .…”
Section: Introductionmentioning
confidence: 99%
“…Hybrid togetherness has characterised the public responses to numerous terror attacks. For example, the public response to the January 2015 shootings at the Charlie Hebdo offices in Paris saw people come together under the banner of the 'Je Suis Charlie' slogan and logo not only on social media but also in the urban spaces of the French capital and other cities (Eroukhmanoff, 2019). However, 'Je Suis Charlie' was also fraught with political tensions and its inference of a universalist frame of belonging was critiqued for erasing social difference and hegemonically amplifying certain groups' perspectives over those of others (Payne, 2018;Lentin, 2019).…”
Section: Introductionmentioning
confidence: 99%